Perceiving screendance through a Laban Movement analysis lens - Munro, Marth (University of Pretoria, 2018)
Screendance as an interdisciplinary practice influenced by the histories of cinema and dance, necessitates a vocabulary aimed specifically at perceiving it as an autonomous art form. This study is a qualitative, practice-based investigation into the ways in which Laban Movement Analysis (LMA) can contribute to the development of a screendance vocabulary. The aim of this study is to observe and analyse the ways in which screendance utilises space. Observation within the context of LMA refers to recognising changes regarding the Body, Effort, Shape and Space patterns discernible in a mover. A perceptive observer will describe the mover’s emerging patterns through an application of the LMA taxonomy (Fernandes 2015:275). Therefore, this observational and analytical approach facilitates an awareness regarding the specific spatial, temporal and energetic qualities attributed to movements, gestures and expressions. The LMA system furthermore, observes and analyses how these movement sequences can become meaningful through various movement combinations (Baron & Carnicke 2008:204). This study is located in the domain of screendance. It aims firstly to observe and analyse excerpts from These Three Rooms (McPherson 1992), Rosas danst Rosas (De Mey 1997) and CoNCrEte (Ginslov 2009) in order to demonstrate the efficacy of an LMA-based vocabulary for screendance. This observation and analysis address the mover’s performance in space. In addition, this process foregrounds the general observable LMA concepts (Body, Effort, Shape and Space) and camera movement, as well as the camera's relationship with the Kinesphere of the mover. This process of observation and analysis serves as an impetus for the second aim of this study, i.e. to interrogate the functionality and expressivity of LMA as a choreographic approach towards screendance. This application suggests a personal, self-reflexion on the creative process followed, as a means of creating a new and original screendance entitled Archi(na)ture (Prinsloo 2017). In order to validate this application of LMA, the study applies the two-layered framework of screendance observation and analysis to Archi(na)ture (Prinsloo 2017). The study concludes that screendance, and particularly space in screendance, is perceivable through LMA as a pragmatic vocabulary when creating screendance, in addition to observation and analysis.